What consumers want in a sustainability food label: Results from online co-creation workshops in the United Kingdom, Ireland and Denmark - Pedersen, Susanne; Benson, Tony; Tsalis, George; Futtrup, Rebecca; Dean, Moira; Aschemann-Witzel, Jessica (Frontiers in Sustainability, 2024)
Changes in consumers’ decision-making relating to food play an important role in the sustainable transition of the food system. However, assessing sustainability across choice alternatives is complex. A holistic or multi-dimensional ‘summary’ sustainability label for food could help consumers make more informed choices, but it is important that such a label is developed taking consumers’ perception and understanding of sustainability into consideration. Hence, it is necessary to understand consumers’ needs and wants in a sustainability food label. The objective of this study is therefore to explore in-depth consumer perceptions and preferences for sustainability as a concept in food production as well as for a sustainability label for food. A total of six online co-creation workshops were carried out in the UK and Ireland (3 groups, n = 24) and Denmark (3 groups, n = 21) using an interactive platform, where participants over the course of two weeks discussed and engaged in creative tasks related to food and sustainability. Results show that consumers in lack information about the sustainability of food products. There were differences with regards to which of 10 pre-tested indicators of sustainability (nature preservation, climate change, animal welfare, fair wages, biodiversity, pollution, health, equality, economic growth and culture) were perceived as most important. The information participants discussed as relevant for a sustainability label included transportation, the degree of processing, and packaging, with some country differences. Consumers acknowledged the complexity of designing and understanding a sustainability food label and existing nutrition labels served as inspiration for creating a sustainability label. Consumers recommended more responsibility to be taken by retailers and food producers through public information campaigns to create awareness. Pros and cons of co-creating a sustainability label with consumers online are discussed as well as the implications for consumers, the food industry and policy makers.